317 PREVALENCE OF MOTORIC COGNITIVE RISK SYNDROME IN PATIENTS WITH MILD COGNITIVE IMPAIRMENT ATTENDING A MEMORY CLINIC. (25th October 2022) - Harte, G; Kennelly, S; Dukelow, T
Abstract: Background: Mild Cognitive Impairment (MCI) alone is not predictive of progression to dementia. However, previous research has found that the combination of MCI and slow gait speed, termed Motoric Cognitive Risk syndrome (MCR), is associated with a three-fold increased risk for the development of dementia. This study aimed to identify the prevalence of MCR among patients with MCI attending a memory clinic at a large teaching hospital. Methods: Participants: Participants were recruited from the memory clinic at the study site. All participants matching the inclusion criteria were invited to participate in the study. Inclusion criteria: Age > 55 years, independently mobile > 50m unaided, diagnosis of MCI. All participants gave informed consent prior to testing. Procedure: Gait speed (in cm/s) during normal pace walking was measured using a 5-metre computerised walkway with embedded sensors (GaitRite). Data Analysis: Gait speed data was dichotomised into "normal" or "low" using previously defined gait speed cut-offs derived from age-based norms. Data was analysed using descriptive statistics on Microsoft Excel. Results: 31 participants completed testing (Males: 12; Females: 19). Mean age was 73.65 (range 63-84). Median score on the Montreal Cognitive Assessment (MoCA) was 20 (range 4-28). N = 2 (6.45%) reached criteria for MCR. Conclusion: Although this study had small numbers, prevalence of MCR was similar to that previously reported among similar populations. This approach to identifying those at high risk for dementia may allow clinicians to target and prioritise further investigations and preventative interventions.